Challenges in Using Medicaid Claims to Ascertain Child Maltreatment. (May 2015) - Raghavan, Ramesh; Brown, Derek S.; Allaire, Benjamin T.; Garfield, Lauren D.; Ross, Raven E.; Hedeker, Donald
Medicaid data contain International Classification of Diseases, Clinical Modification (ICD-9-CM) codes indicating maltreatment, yet there is a little information on how valid these codes are for the purposes of identifying maltreatment from health, as opposed to child welfare, data. This study assessed the validity of Medicaid codes in identifying maltreatment. Participants ( n = 2, 136) in the first National Survey of Child and Adolescent Well-Being were linked to their Medicaid claims obtained from 36 states. Caseworker determinations of maltreatment were compared with eight sets of ICD-9-CM codes. Of the 1, 921 children identified by caseworkers as being maltreated, 15.2% had any relevant ICD-9-CM code in any of their Medicaid files across 4 years of observation. Maltreated boys and those of African American race had lower odds of displaying a maltreatment code. Using only Medicaid claims to identify maltreated children creates validity problems. Medicaid data linkage with other types of administrative data is required to better identify maltreated children.